2022
DOI: 10.1002/advs.202104452
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Derived Extracellular Vesicles Drive T Cell Exhaustion in Tumor Microenvironment through Sphingosine Mediated Signaling and Impacting Immunotherapy Outcomes in Ovarian Cancer

Abstract: SPHK1 (sphingosine kinase-1) catalyzes the phosphorylation of sphingosine to sphingosine-1-phosphate (S1P), is found to be highly expressed in solid tumors. Here, extracellular vesicles (EVs) are identified as the key transporters of SPHK1 to the tumor microenvironment. Consequently, SPHK1-packaged EVs elevate S1P levels in the tumor microenvironment, where S1P appears as an immunosuppressive agent. However, the exact mechanism of how S1P mediates its immunosuppressive effects in cancer is not understood. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 35 publications
(35 reference statements)
0
39
0
Order By: Relevance
“…Among these pathways, those involving MAPK/ERK1/2 and AKT/GSK3β have been associated with HCC proliferation (13), while SPHK1 signaling has been associated with the epithelial-to-mesenchymal transition in HCC (37). SPHK1 induces T cell failure and upregulates the PD-1 ligand, creating an immunosuppressive TME (38,39). Similarly, activation of Wnt/β-catenin, MDM2/ p53, and YAP1 signaling leads to immunosuppression, and blocking such signaling can improve the efficacy of ICIs (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Among these pathways, those involving MAPK/ERK1/2 and AKT/GSK3β have been associated with HCC proliferation (13), while SPHK1 signaling has been associated with the epithelial-to-mesenchymal transition in HCC (37). SPHK1 induces T cell failure and upregulates the PD-1 ligand, creating an immunosuppressive TME (38,39). Similarly, activation of Wnt/β-catenin, MDM2/ p53, and YAP1 signaling leads to immunosuppression, and blocking such signaling can improve the efficacy of ICIs (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…However, certain cell line-based studies showed that ectopic expression of E2F1 could sensitize tumor cells to chemotherapy (etoposide) or radiotherapy in LNCaP or PC3 cells ( 40 , 41 ). Interestingly, a recent study demonstrated that E2F1-mediated transcription is essential for sphingosine-1-phosphate (S1P)-induced upregulation of PD-L1 expression ( 42 ), which may partly explain why FRGPI-high patients responded better to anti-PD-L1 than FRGPI-low patients in our study. Cell division cycle 20 (CDC20) acts as an anaphase-promoting complex activator that controls the proper segregation of chromosomes in mitosis ( 43 ).…”
Section: Discussionmentioning
confidence: 68%
“…In addition, exosomes are nanovesicles that facilitate communication between cells. Exosomes are important in the development and progression of cancer [ 203 ]. Exosomes include functional components such as proteins, lipids, mRNA molecules, and ncRNAs which act as carriers of extracellular information [ 204 ].…”
Section: Therapeutic Approaches For Targeting Ncrnas In CCmentioning
confidence: 99%